Teriparatide Treatment in Patients with Severe Osteoporosis: Effects on Bone Mineral Density, Biochemical Parameters, Back Pain and Quality of Life - Alev Çevikol; Özgür Zeliha Karaahmet; Eda Gürçay; Gülşah Karataş; Ebru Karaca Umay; Aytül Çakcı (Galenos Yayinevi, 2014)
Objective: To evaluate effects of teriparatide therapy on bone mineral density (BMD), biochemical parameters, back pain, and quality of life in patients with severe osteoporosis, who had long-term bisphosphonate treatment. Materials and Methods: Fifteen patients with severe osteoporosis who did not respond to bisphosphonate therapy after an extended period of treatment were enrolled in the study. Teriparatide therapy (20 μq/day) was administered subcutaneously for 12 months as well as 800 IU/day of vitamin D3 and 1200 mg/day of calcium. Patients were evaluated before and after teriparatide therapy in terms of BMD, biochemical parameters, back pain and quality of life. Back pain was assessed by Visual Analog Scale (VAS), and quality of life was assessed by the Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO). Results: The BMD, VAS scale of back pain and all subgroups of QUALEFFO except the social function sub-group showed statistically significant differences before and after treatment. Biochemical parameters did not show any significant difference. Conclusion: Teriparatide therapy may be a good alternative therapy in patients with severe osteoporosis in whom prolonged use of bisphosphonates was present. (Turkish Journal of Osteoporosis 2014;20: 51-5)